Volume Rate Adjustment for Pesticide Applications against Aonidiella aurantii in Citrus: Validation of CitrusVol in the Growers’ Practice - Fonte, Alberto; Garcerá, Cruz; Tena, Alejandro; Chueca, Patricia (MDPI, 2021)
Aonidiella aurantii is one of the most damaging armored scales in citrus crops worldwide. To control this pest, high water volume rates are conventionally used. In order to rationalize the pesticide applications in citrus, IVIA developed CitrusVol, a tool that recommends the optimal volume rate based on the vegetation, the pest or disease and the active ingredient. In this study the objectives were: (I) validate CitrusVol as a tool to adjust the spray volume to control A. aurantii and (II) quantify its environmental and economical advantages. For this, the spray volume adjusted with CitrusVol was compared with the one conventionally used by farmers in 18 applications in seven orchards during two years. The following parameters were evaluated: (I) spray distribution in the canopy, (II) A. aurantii males trapped per day, and (III) number of scales per fruit at harvest. CitrusVol reduced the spray volume and the amount of pesticide by 35% on average. Despite this reduction, a satisfactory spray distribution was achieved, and the volume was found to control the pest in a comparable way to the conventional volume. Moreover, CitrusVol saved per application and on average 31.25 h/100 ha of spray operating time, 241.83 L/100 ha of fuel consumption and consequently, the reduction of emissions of CO2 was 631.18 kg/100 ha. Therefore, CitrusVol allows for efficient, low-input and low-impact pesticide applications.